Lean Operations for Performance Excellence - Nawanir, Gusman; Lim, Kong Teong; Maarof, Mohd Ghazali (Suara UMP, 2020)
Originated from the shop floors of the Japanese automobile industry, in particular, Toyota Motor Corporation (TMC), in the late 1950s to early 1960s (Monden, 1983; Ohno, 1988), lean manufacturing has received much attention all over the world. The success of the TMC in implementing lean manufacturing attracted other Japanese manufacturers since 1973, as Toyota gained huge profits, while others suffered several losses. This encouraged other manufacturers to implement the same principles to leverage their organizational performance.